2016
DOI: 10.1080/19490976.2016.1182288
|View full text |Cite
|
Sign up to set email alerts
|

H2metabolism is widespread and diverse among human colonic microbes

Abstract: Microbial molecular hydrogen (H 2 ) cycling is central to metabolic homeostasis and microbial composition in the human gastrointestinal tract. Molecular H 2 is produced as an endproduct of carbohydrate fermentation and is reoxidised primarily by sulfate-reduction, acetogenesis, and methanogenesis. However, the enzymatic basis for these processes is incompletely understood and the hydrogenases responsible have not been investigated. In this work, we surveyed the genomic and metagenomic distribution of hydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 50 publications
3
115
0
2
Order By: Relevance
“…1). In vitro studies have shown that members of the genera Roseburia, Ruminococcus, and Eubacterium generate H 2 [25]. Another means of microbial H 2 production is through the oxidation of reduced ferredoxin (Fd) and pyridine nucleotides by microbial hydrogenases.…”
Section: Short-chain Fatty Acid Production In the Large Intestinementioning
confidence: 99%
“…1). In vitro studies have shown that members of the genera Roseburia, Ruminococcus, and Eubacterium generate H 2 [25]. Another means of microbial H 2 production is through the oxidation of reduced ferredoxin (Fd) and pyridine nucleotides by microbial hydrogenases.…”
Section: Short-chain Fatty Acid Production In the Large Intestinementioning
confidence: 99%
“…Microbial hydrogenogenesis and hydrogenotrophy involves the reversible oxidation of H 2 by hydrogenase harboring organisms. Categorized by their metal functional cores, hydrogenases are phylogenetically widespread and functionally diverse and include both hydrogen evolving and hydrogen uptake [NiFe] hydrogenases, hydrogen evolving [FeFe] hydrogenases, and hydrogen uptake [Fe]‐only hydrogenases . Hydrogenotrophic microbes utilize hydrogen to convert carbon dioxide to acetate (i.e., acs , fhs genes), methane ( mcrA gene), and hydrogen sulfide ( dsrA gene) .…”
Section: Introductionmentioning
confidence: 99%
“…Categorized by their metal functional cores, hydrogenases are phylogenetically widespread and functionally diverse and include both hydrogen evolving and hydrogen uptake [NiFe] hydrogenases, hydrogen evolving [FeFe] hydrogenases, and hydrogen uptake [Fe]only hydrogenases. 10 Hydrogenotrophic microbes utilize hydrogen to convert carbon dioxide to acetate (i.e., acs, fhs genes), 11 methane (mcrA gene), 12 and hydrogen sulfide (dsrA gene). 13 Conceivably, low methane production may reflect low hydrogenotrophic methanogenic abundance or low substrate availability (i.e., hydrogen), perhaps due to fewer hydrogenogenic microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous H 2 is catalyzed and produced by hydrogenases (H 2 ases) in bacteria, such as Escherichia coli, Bacteroidetes and Firmicutes in colon [3-5]. The great majority of H 2 ases contain iron-sulfur clusters and two metal atoms at their active center, a Ni and a Fe atom, the [NiFe]-H 2 ases, or two Fe atoms, the [FeFe]-H 2 ases [6].…”
Section: Hydrogen Gas-background To It Usementioning
confidence: 99%